Politics and Social Cohesion in Grassroots of Karnali, Nepal - Bishwakarma, Kripa Ram (Humanities and Social Sciences Journal, 2024)
The present study argues that ethical entrepreneurship in a society plays significant roles in development, participation and comprehensive peacebuilding. The leading institutions should make the followers realize their convincing and transparent demeanor in every performance. It is an explorative study with qualitative design. The sampling is purposive and the site is Aathabis Municipality, Dailekh. The data were collected from 21 respondents in total (including 12 Key Informant Interviews and 9 from focus group discussion) accompanied with the secondary data. Students, teachers, professionals and the executive social workers are the sources of information. The data analysis is synchronic and presentation has been systematic. Adopting the mores and standard of study, it has focused on the politics and social cohesion in the grassroots communities of Aathabis Municipality of Dailekh a hill district of Karnali Province of Nepal. It will be significant tool for all those individuals that have kin interest in social sciences research and social innovation.